Identifikasi Ketidaklengkapan Dokumen Rekam Medis Rawat Inap Di RS Tentara Tk. III dr. Reksowidiryo Padang - Syahpikal Sahana; Budi Justitia; Yopy iskandar; Vip Paramarta (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Medical record documents are very important in process of services performed by medical personnel and the hospital's quality of care. by medical officers and affect the quality of a hospital's services. The purpose of this study was to identify factors that influence the incompleteness of inpatient medical record documents at RST Tk. III dr. Reksowidiryo Padang. The data analysis used is qualitative analysis. The observations were conducted from October 1, 2023 to October 30, 2023. The data taken are medical record documents submitted from the inpatient unit to the medical records sub-section on those particular days. The results of data analysis show that the lowest assessment is for filling out documents by doctors. From the results of the description of the problem in the Ishikawa diagram, the most fundamental issue influencing incomplete medical record documents is the doctor's lack of discipline.